A systematic review on autistic people's experiences of stigma and coping strategies. Issue 1 (8th December 2021) - Han, Emeline; Scior, Katrina; Avramides, Katerina; Crane, Laura
Abstract: Autism can be understood as a concealable stigmatized identity. This is the first systematic review to synthesize the literature on autistic people's experiences of stigma and coping strategies. 2877 studies were screened and 27 were included in this review. The reviewed literature demonstrates that autistic individuals are acutely aware of being stereotyped, judged, and discriminated by others. Autistic people also show signs of internalizing stigma, rendering them more vulnerable to low self‐worth and poorer mental health. To manage the impact of stigma, the included studies suggest that autistic individuals may use these strategies: concealment and camouflaging, selective disclosure and self‐advocacy, as well as positive reframing and reconstructing identity. However, the evidence is limited and mixed in terms of how helpful and effective these strategies are. Future studies should include autistic populations with a wider range of intellectual abilities and explore interventions that can support autistic people in managing stigma to supplement interventions that seek to reduce stigma towards autistic people. The power of language in perpetuating and challenging stigma also has important implications for research and practice, underscoring the need for researchers and practitioners to reflect carefully on the messages they are communicating about autism. Lay Summary: This review has found that autistic people often experience stigma, which refers to negative attitudes and treatment from others. Because of that, some autistic people also have negative beliefs about themselves, which may affect their self‐worth and mental health. While research suggests that autistic people use a range of strategies to manage stigma, the evidence is limited and mixed in terms of how helpful these strategies are.